Healthy Aging and Physical Activity: The Qualitative Research (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Population aging is a global trend encouraging countries and their governments to introduce different policies related to the increasing number of older adults. Also, on the individual level, people can contribute to healthy aging by performing regular physical activity. Physical activity improves next-day job performance and health. Additionally, a recent study from Harvard Business Review found that even a short time of physical activity (20 minutes per day) was sufficient to benefit employees' next-day performance and health. The goal of this study is to deepen the knowledge of healthy aging, specifically, related to senior adult health and wellness management. To study the phenomena, we employed qualitative research by integrating the coaching perspective through the expert opinion of Gregor Sobočan, Master of Sport International Class and head coach of professional athletes in the Slovenian national sports team at the national level, and senior participants, athletes in the Kettlebells Center sports club in Ljubljana, Slovenia. Namely, we collected their opinions and performed the content analysis. The research outlined that regular physical activity and active and healthy aging are vital for human health, in line with the integrative body-mind-spirit framework.